Manajemen Privasi pada Pengguna Media Sosial Instagram - Ferisa Nurul Kamilah; Sri Budi Lestari (Interaksi Online, 2021)
The emergence of the phenomenon of the use of social media Instagram, which is used as a suggestion to make self-disclosure. Self-disclosure includes things that include the realm of user privacy. This can pose a variety of risks that can occur to Instagram users. This research aims to reveal and understand how a person does privacy management on his Instagram account by using qualitative research methods. This research refers to interpretive paradigms with phenomenological approaches. The data collection technique used in this study is indepth interview, with the number of informants as many as 5 people. The theory used in this research is Communication Privacy Management Theory put forward by Sandra Petronio. The results of this study revealed that users use Instagram to create impressions, interests, relationships and build their image. In addition, users also have different restrictions on information regarding their privacy. Through communication privacy management theory also found that there are rules criteria used by Instagram users to consider when to disclose information through Instagram. Cultural criteria such as customs, norms, and religious values that exist in the user, gender criteria in the form of gender expression and clothing, motivation criteria in the form of encouragement and feeling of pleasure, context criteria in the form of positiveness, not offensive to others, and environmental conditions, risk criteria - benefits that is a comparison between the amount of profit or loss that the user will get after making disclosure. In this study, the way that users manage their Instagram privacy is by deciding not to disclose their privacy at all on Instagram or creating a second Instagram account devoted to disclosing privacy. The second account used is only shared by the people closest to them and trusted by the user who makes it more free to express their privacy.